Feasibility for Using Thermography Throughout an Exercise Program in Mastectomized Patients - das Virgens Aquino, Maria Jane; dos Santos Leite, Paula Michele; Lima Rodrigues, Ingrid Kyelli; DeSantana, Josimari Melo (Frontiers in Oncology, 2022)
Introduction: Breast cancer is the most common in the female population. Physical training is safe and indicated after surgical treatment for breast cancer. During exercise, body temperature changes due to tissue metabolic activity, in this sense, infrared thermography is used to map the thermal patterns of the body surface. Objective: to evaluate the feasibility of using thermography during a physical rehabilitation program in mastectomized patients by analyzing the change in body temperature caused by physical exercise in the breast region. Methodology: This is a simple and covert clinical trial, in which the sample was constituted for convenience. The women were submitted to a supervised physical exercise protocol, three times a week, for 20 sessions. They were evaluated in the first, tenth and twentieth sessions in relation to changes in body temperature in the breast region (Infrared Thermography). Results: 20 patients who underwent mastectomy surgery were recruited. No patient had drain infection, scar dehiscence or lymphedema, and only one patient had to remove seroma. The mean age was 50.45 ± 2.00 years and the Body Mass Index (BMI) was 28.95 ± 1.11 kg/m². In the body thermography of the patients' breast region, no significant difference was observed when comparing the thermograms of the plastron region of the patients in the first, tenth and twentieth sessions (p=0.201). However, when comparing the plastron region with the control breast, a reduction in temperature was observed in the operated region in the first (p=0.012) and in the tenth sessions (p=0.004). Conclusion: Through this study, we can conclude that the use of infrared thermography is viable for the analysis of the body temperature of mastectomized patients during a supervised physical exercise protocol and, therefore, suggest that this instrument is increasingly used with the cancer public.